Analysis of shaking-induced cherry fruit motion and damage. (April 2016) - Zhou, Jianfeng; He, Long; Karkee, Manoj; Zhang, Qin
Abstract : High percentage of shaking-induced fruit damage is the major obstacle for mechanical harvesting of fresh-market sweet cherry. This study focused on the evaluation of the effect of vibration frequency on fruit motion, detaching time and damage during mechanical cherry harvesting with a shaker. A high-speed camera was used to capture the fruit trajectory on eighteen limbs excited at the frequencies of 10, 14 and 18 Hz. Fruit detaching time and number of fruit-to-fruit and fruit-to-limb impact were extracted from the high speed videos for determining the factors affecting fruit removal and damage. Results showed that the majority of the four identified motion patterns were tilting and beam-column motion, accounting for more than 70% of all patterns. Fruit detaching time was significantly affected by vibration frequency with fast detaching at high frequencies. Vibration frequency affected the overall fruit damage percentage substantially, with the lowest damage percentage of 47.1% in 14 Hz, which might be caused by high percentage of beam-column motion during vibration at the frequency. Meanwhile, 18 Hz vibration resulted in a higher percentage (35%) of unmarketable fruits than that of 10 Hz and 14 Hz. On average, a fruit experienced 3.8 impacts against limbs and other fruit at 18 Hz excitation, substantially lower than that of 11.8 impacts at 14 Hz or 11.7 impacts at 10 Hz excitation. Overall, the results indicate that shorter duration of high-level mechanical impacts could induce higher fruit damage. Highlights: More tilting and beam-column motions are found in vibration harvesting. Fruit detaching time may be improved using properly designed trellis system. 14 Hz vibration resulted in the least damage and a shorter fruit detaching time. High frequency vibration results in more serious damage with less impact times.